Active methodologies based on digital skills to improve academic performance - Fernández Jiménez, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The present research aims to demonstrate the relationship of the improvement of academic performance and mastery of three digital competencies: digital information management and communication in the digital environment, collaboration and, creation of digital content when used by the university student in their active learning process, how they encode the information they learn, how they communicate their development and how they create their knowledge to fulfill a purpose of improvement in their grades and academic improvement.